PATH COEFFICIENT IN SAFFLOWER AS AFFECTED BY HARVEST DATES - & et al., Wuhaib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In order to determine the traits that correlate to yield to rely on them as selection criteria for high yield in safflower; seeds of five cultivars .2081, Gelser Almais , Ordini, and rabia 500 planted in the field of Field Crop Dept. College of Agriculture –Uni. Of Baghdad during 2010and 2011.The design of experiments is randomize complete block design with split plot arrangement with three replication. Data were recorded for traits: yield/ plant, total yield, harvest index, oil%, number of seed/plant, number of seeds/capsules, seed weight,dry weight of plant, number of capsules/plant, number of primary and secondary branches and plant height. Results of statistical analysis illustrate that the genotypic and phenotypic correlation and direct and indirect effects were different due to differences in harvest dates and tow years of planting.The highest positive genetic correlation and direct effects with yield were for plant height and total yield for first harvest in first year, for second year were dry weight, number of capsules/ plant, number of seed/ plant and total yield. For second harvest in first year was total yield only. and number of capsule/ plant, dry weight, total yield and number of seeds/ plant, in second year. Also only total yield in third harvest in first year, and dry weight and total yield in second year. In fourth harvest first year the traits were number of capsulesand total yield, dry weight and total yield in second year. For that we can rely these traits as criteria for selection in breeding programs to improve the yield of safflower.